ENVIRONMENT HIKAYAT 7 PUTRI MALUKU UTARA SEBAGAI MEDIA KOMUNIKASI MASSA - Raharjaan, Jerry Dounald; Herlina, Elin; Kusuma, Sigit Setya (Universitas Swadaya Gunung Jati, 2024)
Among the numerous verbal narrative structures in the archipelago, Hikayat stands out as one of the oral traditions that has flourished in the eastern regions of the archipelago, particularly in the North Maluku area. One of the Hikayats that has gained widespread popularity in North Maluku society is the Hikayat 7 Putri. This Hikayat is believed to be the genesis or foundation of establishing four major Sultanates in North Maluku: the Sultanates of Jailolo, Bacan, Tidore, and Ternate. Based on the abovementioned description, conducting an in-depth study or research regarding the environment depicted in the Hikayat 7 Putri is necessary. The narrative unfolds various structures describing the environment (location) where the story takes place. The narration delves into the terrestrial-sky-terrestrial region, which serves as the primary setting in the story. From the visualization of this environment, it could potentially become an effective medium of mass communication. In examining or researching the Hikayat 7 Putri of North Maluku, various theoretical approaches are required to dissect its narrative structure. The visual narrative theory serves as the primary analytical tool in this study, and it is complemented by the ecological (ecosystem) theory in exploring the cultural (geographical) data of North Maluku society. The Visual Narrative theory is considered capable of dissecting the story's environmental structure (location) in the North Maluku region, which serves as the Ecological (ecosystem) structure of the Hikayat 7 Putri itself. Consequently, this narrative approach can be visualized broadly and translated in detail through scientific analysis, serving as an effective medium of mass communication. Keywords: Tale of the 7 Princesses of North Maluku, Visual Narrative, Environment, Ecology, Mass Communication